Exiguobacterium enclense sp nov., isolated from sediment - Dastager, Syed Gulam; Mawlankar, Rahul R.; Sonalkar, Vidya V.; Thorat, Meghana N.; Mual, Poonam; Verma, Ashish; Krishnamurthi, Srinivasan; Tang, Shan-Kun; Li, Wen-Jun (International Journal of Systematic and Evolutionary Microbiology, 2015)
A Gram-stain-positive bacterium, designated strain NIO-1109(T), was isolated from a marine sediment sample from Chorao Island, Goa, India. Phenotypic and chemotaxonomic characteristics and data from phylogenetic analysis based on 16S rRNA gene sequences indicated that strain NIO-1109(T) was related to the genus Exiguobacterium. Strain NIO-1109(T) exhibited >98.0% 16S rRNA gene sequence similarity with respect to Exiguobacterium indicum HHS 31(T) (99.5%) and Exiguobacterium acetylicum NCIMB 9889(T) (99.1 %); the type strains of other species showed <98% similarity. Levels of DNA DNA relatedness between strain NIO-1109(T) and E. acetylicum DSM 20416(T) and E indicum LMG 23471(T) were less than 70% (33.0 +/- 2.0 and 37 +/- 32%, respectively). Strain NIO-1109(T) also differed from these two closely related species in a number of phenotypic traits. Based on phenotypic, chemotaxonomic and phylogenetic data, strain NIO-1109(T) is considered to represent a novel species of the genus Exiguobacterium, for which the name Exiguobacterium enclense sp. nov. is proposed. The type strain is NIO-1109(T) (=NCIM 5457(T)= DSM 25128(T)=CCTCC AB 2011124(T)).